Wear Scar Characterization of Polycarbonate Urethane (PCU) By Raman Spectroscopy - Wahyu Dwi Lestari; Luluk Edahwati; Ndaru Adyono; Tria Puspa Sari; Wiliandi Saputro; Ahmad Khairul Faizin; Radissa Dzaky Issafira (Future Science)
Until now, the need for revision surgery and implant failure is still the main clinical problem in installing biomaterials in the human body. Mechanical testing is needed to determine the life of the biomaterial before it is implanted in the human body. Mechanical testing in this study was carried out using a pin on discs simulator, run for 50000 cycles in dry condition. PCU material is used as disc components and SS 316L as a pin. The following test parameters were used: normal load FN = 500 gram and sliding velocity 50 Rpm in dry condition. Chemical changes in the wear scar can cause a drift in friction level. This study aims to analyze the chemical surface changes in wear tracks of PCU after mechanical testing. For this, Raman spectroscopy was used to determine the chemical changes at the surfaces. The wear tracks developing between the metal on PCU were analyzed using these techniques. The results show that the chemical changes in the wear scars of the PCU disc are due to mechanical stress. Raman spectroscopy is used to observe the chemical changes on the wear scar due to the sliding test.